(untitled) (REDEL. Revista Granmense de Desarrollo Local, 2023)
Total anomalous connection of pulmonary veins is a complex and critical Congenital Heart Disease, in which all the pulmonary veins drain incorrectly into the right side of the heart. The four pulmonary veins connect to a collector that carries blood to the right atrium directly or through systemic venous drainage, so, the oxygenated blood from the pulmonary circulation does not reach the left side of the heart, so it does not leave through the aorta to nourish the body. The objective of the article is to describe the clinical-ultrasound and electrical manifestations of an infant with a diagnosis of Total Anomalous Connection of Pulmonary Veins. A clinical case presentation of a patient seen in the cardiology clinic of the Hermanos Cordové Pediatric Hospital and a review of the bibliography through search engines, meta-search engines and databases (Google Scholar, PubMed, ScienceDirect and Scopus) were carried out. The clinical ultrasound and electrical diagnosis of a critical and complex heart disease was made in secondary health care and its subsequent optimal referral to the William Soler Pediatric Cardiocenter, Havana where corrective surgery was performed that allowed the restoration of cardiovascular functionality. The multidisciplinary approach to congenital heart diseases from the fetal stage is of vital importance, since it allows adequate follow-up and timely treatment to improve the quality of life of patients.